Giftedness, Gender Identities, and Self-Acceptance: A Retrospective Study on LGBTQ+ Postsecondary Students. (July 2022) - Lo, C. Owen; Hu, Shun-Fu; Sungur, Hasan; Lin, Ching-Hui
In a recent position statement, the National Association of Gifted Children argued the importance of providing equitable treatment of Lesbian, Gay, Bisexual, Transgender, Queer and other sexual and gender minority individuals (LGBTQ+) gifted youth to help them maximize their potential. However, there are very few empirical studies focusing on the intersection of giftedness and gender identities. Little is known regarding these students' experience at, and outside of, school. Focusing on the individual process of gender identity development and self-acceptance, we interviewed nine LGBTQ+ postsecondary students in North America (aged between 19 and 29 years) who are graduates of an academically focused high school in Turkey. In particular, we studied their ways of thinking, stress coping strategies, and environmental factors that may have enabled their self-acceptance of LGBTQ+ identities. Findings of the study show that the mental health of LGBTQ+ is a function of individual factors (e.g., coping strategies), structural factors (e.g., a homophobic sociocultural environment), and the context. The findings also indicate the benefits of complexity and reflectiveness in thinking, metacognition and the ability to separate identity labels from identities, enabled by high school peer support, liberal curriculum and classroom discussions, and access to information during adolescence.